2021
DOI: 10.1097/qad.0000000000002935
|View full text |Cite
|
Sign up to set email alerts
|

Using an electronic health record alert to prompt blood-borne virus testing in primary care

Abstract: Background: Late diagnosis of HIV, hepatitis B (HBV) and hepatitis C (HCV) remains relatively common in the UK and many people who present late have missed opportunities for testing in primary care. The objective was to assess the effectiveness and acceptance of a prototype application (BBV_TP1), embedded in a primary care electronic health record (EHR), to increase real-time blood-borne virus (BBV) testing.Methods: This prospective cohort study assessed BBV_TP1 in 14 general practices in North East England, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
(22 reference statements)
0
7
0
1
Order By: Relevance
“…This particular prompt, compared with other prompts, was considered simple to understand and easy to manage The prompt in the context of the consultation - Most discussed blood tests and submitted an order with the patient present. Some GPs ordered the test after the patient had left and were faced with the dilemma of whether to bring the patient back to discuss HIV testing - Many hospital-based and general practice HCWs felt the prompt was too late in the ordering process and disrupts the consultation, potentially opening up a new topic, causing irritation Perception Impact on time: Mixed views Driving perception: Either: - no mention of time - prompt causes test to be ordered after consultation - disruptive if prompt comes too late in the ordering process - potentially opens up a new topic right at the end of the consultation Chadwick et al 2021 [ 100 , 101 ] UK To evaluate a prototype application designed to prompt in real-time, BBV testing in previously untested higher risk individuals attending primary care Condition of focus : Blood-borne viruses Setting : General practice Tool : CDS to identify patients at risk of blood-borne viruses - Embedded/linked with EMR: Yes - Interruptive alert: Yes - User-driven: Clinician - Risk score: Yes Prospective cohort study Number of 'hard prompts' and clinicians' responses BBV tests ordered Survey of GPs Clinicians’ perceptions of the prompt system were positive with average additional time required for BBV test discussion in consultations estimated at 2 min Nineteen percent of clinicians reported having to make an additional appointment after a BBV test prompt because of insufficient time during a consultation and 15% had to make an additional appointment to discuss test results Free-text answers stressed the lack of time available Median additional consultation time varied from 0.25 min when the clinician ignored the prompt to 2 min when the prompt was accepted or declined Perception Impact on time: Increase Driving perception: limited time during consultations Chima et al 2019 [ 102 ] UK To summarise existing evidence on the effects of eCDSTs on decision making for cancer diagnosis in primary care, and determine factors that influence their successful implementation Condition of focus: Cancer Setting : General practice Tool : Range of CDS tools to support cancer diagnosis - Embedded/linked with EMR: Range - Interruptive alert: Range - User-driven: Range - Risk score: Range Systematic review …”
Section: Resultsmentioning
confidence: 99%
“…This particular prompt, compared with other prompts, was considered simple to understand and easy to manage The prompt in the context of the consultation - Most discussed blood tests and submitted an order with the patient present. Some GPs ordered the test after the patient had left and were faced with the dilemma of whether to bring the patient back to discuss HIV testing - Many hospital-based and general practice HCWs felt the prompt was too late in the ordering process and disrupts the consultation, potentially opening up a new topic, causing irritation Perception Impact on time: Mixed views Driving perception: Either: - no mention of time - prompt causes test to be ordered after consultation - disruptive if prompt comes too late in the ordering process - potentially opens up a new topic right at the end of the consultation Chadwick et al 2021 [ 100 , 101 ] UK To evaluate a prototype application designed to prompt in real-time, BBV testing in previously untested higher risk individuals attending primary care Condition of focus : Blood-borne viruses Setting : General practice Tool : CDS to identify patients at risk of blood-borne viruses - Embedded/linked with EMR: Yes - Interruptive alert: Yes - User-driven: Clinician - Risk score: Yes Prospective cohort study Number of 'hard prompts' and clinicians' responses BBV tests ordered Survey of GPs Clinicians’ perceptions of the prompt system were positive with average additional time required for BBV test discussion in consultations estimated at 2 min Nineteen percent of clinicians reported having to make an additional appointment after a BBV test prompt because of insufficient time during a consultation and 15% had to make an additional appointment to discuss test results Free-text answers stressed the lack of time available Median additional consultation time varied from 0.25 min when the clinician ignored the prompt to 2 min when the prompt was accepted or declined Perception Impact on time: Increase Driving perception: limited time during consultations Chima et al 2019 [ 102 ] UK To summarise existing evidence on the effects of eCDSTs on decision making for cancer diagnosis in primary care, and determine factors that influence their successful implementation Condition of focus: Cancer Setting : General practice Tool : Range of CDS tools to support cancer diagnosis - Embedded/linked with EMR: Range - Interruptive alert: Range - User-driven: Range - Risk score: Range Systematic review …”
Section: Resultsmentioning
confidence: 99%
“…121 Some studies (n = 10) mentioned 'alert fatigue' indicating that eCDS tools designed to support health professionals can increase the number of on-screen alerts, leading to a high chance of them being missed or ignored. 15,35,38,97,112,117,[122][123][124][125] None of these studies reported a decrease in consultation duration.…”
Section: Methods To Measure Consultation Durationmentioning
confidence: 95%
“…Twenty-three of these reported the impact on 'work ow', regarding how eCDS tools altered the usual order in which patient-related tasks were carried out. 33,35,38,57,61,62,64,80,86,89,97,102,104,105,108,[113][114][115][116][117][118][119][120] Five referred to the impact of using eCDS tools on the trajectory of dialogue with patients, to the extent that follow-up appointments were arranged to avoid consultations running late. 35,72,114,115,118 One of these mentioned clinicians' concerns about 'taking time away' from other waiting patients, expressed as a barrier to the implementation of eCDS systems.…”
Section: Methods To Measure Consultation Durationmentioning
confidence: 99%
See 2 more Smart Citations